“[T]he most precise and thorough understanding of the situation we are struggling to change”: re-capturing emancipatory disability research - Beesley, Luke (Frontiers in Sociology, 2025)
This article seeks to contribute to a refoundation of the analytic, qualitative and quantitative methods associated with Emancipatory Disability Research (EDR)—an episto-political approach to disability research which places lay disabled people in positions of authority over research design, operation, and analysis of projects undertaken by professional academics. The argument of this article is that a significant reason for EDR's meager impact on political practice, the burnout and disillusionment of some of its most talented proponents, and its failure to develop beyond limited applications in sociology and disability studies lies in the disjointed and asymmetrical development of its aims and methods. I indicate, particularly, that the core evaluation signifiers for EDR's success (that disabled people concretely benefit from the research, and control both its future direction and the uses made of it) rested on an initial demand from disabled activists for scientific rigor and a realist ontology in research which were subsequently rejected by EDR's academic advocates. Without a grounding in the scientific method, a meta-theory of subject-object relations and knowledge, or an evaluative framework for the objective accuracy of input concepts; EDR's research framework prevented practitioners from producing outputs for which there was a demonstrable demand, while promising forms of research for which there was not.